An Overview of the Advances in Research on the Molecular Function and Specific Role of Circular RNA in Cardiovascular Diseases. (18th August 2022) - Yin, Lianli; Tang, Yinghua; Yuan, Yulin
Abstract : In recent years, the rate of residents suffering from cardiovascular disease (CVD), disability, and death has risen significantly. The latest report on CVD in China shows that it still has the highest mortality rate of all diseases in that country. Different from linear RNA, circular RNA (circRNA) is a covalently closed transcript, mainly through reverse splicing so that the 3′ end and the 5′ end are covalently connected to form a closed loop structure. It is structurally stable and abundant and has distinct tissue or cell specificity, and it is widely distributed in eukaryotes. Although circRNAs were discovered many years ago, researchers have only recently begun to slowly discover their extensive expression and regulatory functions in various biological processes. Studies have found that some circRNAs perform multiple functions in cells more used as RNA binding protein or microRNA sponge. In addition, accumulating evidence shows that the first change that occurs in patients with various metabolic diseases such as hypertension and cardiovascular disease is dysregulated circRNA expression. For cardiovascular and other related blood vessels, circRNA is one of the important causes of various complications. These findings contribute to a more comprehensive understanding and grasp of CVD, and the related molecular mechanisms of CVD should be further analyzed. Here, we review the new understanding of circRNAs in CVD and explain the role of these innovative biomarkers in the analysis and determination of other related cardiovascular events such as coronary heart disease. Thus, this study is aimed at providing new ideas and proposing more feasible medical research strategies based on circRNA.